Hubungan Antara Dukungan Sosial Dan Strategi Coping Dengan Kebahagiaan Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Alvionita, Fera; Damayanti, Rika; Yulianti, Iin; Syafrimen, Syafrimen (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine the relationship between social support and coping strategy with happiness in students who are working on their thesis. The population in this study were students of the 2018 Islamic Counseling Guidance Study Program with a total sample of 70 students selected using the simple random sampling technique. This study uses the happiness scale, social support scale and coping strategy scale. Data analysis uses multiple regression analysis techniques assisted by the JASP software version 0.16.1.0 for windows. The first hypothesis test produces an R value = 0,582 and an F = 17.128 value with a significant level of P <0.01 these result indicate that there is a significant relationship between social support and coping strategies with happiness. The two independent variables make an affective contribution of 33.8%. In the second hypothesis test, the correlation value (rx₁-y) = 0.538 with a significance value of P = < .001 shows that prove that there is a significant relationship between social support and happiness. The social support variable makes an affective contribution of 23.3%. In third hypothesis test, the correlation value (rx₂-y) = 0.430 with a significance value of P = < .001 shows that there is an affective significant relationship between coping strategies and happiness. Coping strategy variables provide contribution relationship of 10.5%.Keywords: Happiness, Social Support, Coping Strategy